Capacity Utilisation in the Malaysian Palm Oil Refining Industry - Abdul Jalil, Suhaila (1996)

(untitled)
This thesis examines the economic structure and performance of Malaysian palm oil refining industry with emphasis on both capacity utilisation (CU) of the individual refineries and the overall industry. The specific objectives of the study are: firstly, to explain the general economic development of the palm oil refining industry particularly from the perspective of policies that have been instrumental in shaping the progress of the industry; secondly, to elucidate the general market structure characteristics of the industry; thirdly, to assess the industry's performance pertaining to its CU from the perspective of its demand for the four factor inputs, namely; capital, labour, electricity and fuel; finally, to draw policy implications and recommendations. The structural dimensions studied are the degree of market concentration and the extent of capacity utilisation in the palm oil refining industry. The industry concentration is measured by using concentration ratio or indices commonly used by industrial economists, to show simple descriptive statistics of concentration ratio of the larger firms in the industry. The economic capacity output of the refining industry is analysed using the framework of cost and production function following Berndt and Hesse. The economic theory employed in the study is to specify, estimate and interpret the capacity output (CO) and CU measure of the twenty-one refineries within the oil palm refining industry for 1990 and 1991, using pooled time-series and cross-sectional data. CU is defined as the ratio of actual output to capacity output that measures the output gap that exists when actual output differs from capacity output. The framework is empirically implemented by estimating the restricted translog variable cost function with single output. The parameter estimates of the factor demand function are derived using the Ordinary Least Square technique, and elasticities of substitution of the parameter estimates are computed to evaluate the refinery's demand for inputs. The capacity output is estimated through an iterative technique, using the C-Ianguage Programming package, as it is not possible to be estimated through analytical or closed-form solution. The effect of change in price of the variable inputs on capacity output and CU is also being assessed. The result of the four-firm concentration ratio indicates that the market share of the largest few firms from 1988-1992 comes to 40 per cent. It shows strong attributes of a workably competitive market where there is lack of government supervision, unstable market share, flexible pricing, low barriers to entry, very little collusion and very low profit. The CD estimates point to pervasive and chronic excess capacity in all the refineries examined with the exception of one firm whose CU ratio was more than unity in both years, 1990 and 1991. This indicates the sluggishness of investment in this particular sector of the economy. Demand condition for the four factor inputs has been found to remain inelastic. An examination of the effects of change in price of electricity, fuel, labour and capital on CU shows an insignificant effect on the refiners' decision to refine. These findings imply that investment in capacity and capacity utilisation by all the refineries in the industry may be influenced by factors that are external to the refineries, for instance increased demand and price of RPO in the world market, or a decrease in domestic price of CPO, regardless of the price of the inputs.